Pavement ant Tetramorium caespitum (Linnaeus) (Insecta: Hymenoptera: Formicidae) - Tyler Vitone; Andrea Lucky (EDIS)
The pavement ant is one of the most commonly encountered ants in the United States. Since first introduced from Europe at the beginning of the nineteenth century, the ant has become well established and is prevalent in urban areas in the northern U.S. and parts of Canada. However, the extent of their invasiveness and severity as a pest is not well characterized. This 5-page fact sheet was written by Tyler Vitone and Andrea Lucky, and published by the UF Department of Entomology and Nematology, September 2014.